2004
DOI: 10.1074/jbc.m311956200
|View full text |Cite
|
Sign up to set email alerts
|

Both Insulin Signaling Defects in the Liver and Obesity Contribute to Insulin Resistance and Cause Diabetes in Irs2–/– Mice

Abstract: We previously reported that insulin receptor substrate-2 (IRS-2)-deficient mice develop diabetes as a result of insulin resistance in the liver and failure of ␤-cell hyperplasia. In this study we introduced the IRS-2 gene specifically into the liver of Irs2 ؊/؊ mice with adenovirus vectors. Glucose tolerance tests revealed that the IRS-2 restoration in the liver ameliorated the hyperglycemia, but the improvement in hyperinsulinemia was only partial. Endogenous glucose production (EGP) and the rate of glucose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 61 publications
4
50
1
Order By: Relevance
“…To verify the hypothesis, we investigated the gene expression in the WAT of Irs2 Ϫ/Ϫ mice and ob/ob mice after continuous intracerebroventricular infusion of leptin. Leptin infusion at a rate of 300 ng/h yielded lean Irs2 Ϫ/Ϫ mice and overcame their leptin resistance as previously reported (17), and it reduced DGAT2 mRNA expression by about 60% in the WAT of Irs2 Ϫ/Ϫ mice whereas it significantly increased DGAT1 expression (Fig. 6, a-c).…”
Section: Intracerebroventricular Infusion Of Leptin Reduced Dgat2supporting
confidence: 54%
See 2 more Smart Citations
“…To verify the hypothesis, we investigated the gene expression in the WAT of Irs2 Ϫ/Ϫ mice and ob/ob mice after continuous intracerebroventricular infusion of leptin. Leptin infusion at a rate of 300 ng/h yielded lean Irs2 Ϫ/Ϫ mice and overcame their leptin resistance as previously reported (17), and it reduced DGAT2 mRNA expression by about 60% in the WAT of Irs2 Ϫ/Ϫ mice whereas it significantly increased DGAT1 expression (Fig. 6, a-c).…”
Section: Intracerebroventricular Infusion Of Leptin Reduced Dgat2supporting
confidence: 54%
“…We previously reported that increased expression of sterol regulatory element binding protein-1 (SREBP-1) mRNA in the liver of Irs2 Ϫ/Ϫ mice causes fatty liver, and we attributed its development to leptin resistance (16). We have also reported that the obese phenotype in Irs2 Ϫ/Ϫ mice contributes to their insulin resistance (17).In this study, we discovered that the adipocytes of Irs2mice are hypertrophic and concluded that fatty acid and triglyceride synthesis must be activated in Irs2 Ϫ/Ϫ mouse adipocytes. Screening for genes involved in the fatty acid and triglyceride synthesis pathways revealed that DGAT2 mRNA was significantly up-regulated in Irs2 Ϫ/Ϫ mouse white adipose tissue (WAT) but that expression of DGAT1 was reduced.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…There are several related IRS family members, including IRS-2, IRS-3, IRS-4, Gab-10, and p62 dok . IRS-2 has overlapping signaling potential, but does not restore insulin sensitivity in IRS-1 knockout mice (Suzuki et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Irs proteins lie downstream of the Insr and Igf-1r. Female Irs2 knockout mice showed infertile, hyperphagic, leptin resistant and developed obesity [100,101]. Mice lacking Irs2 in both pancreatic bcell and hypothalamic neuronal population using a rat insulin 2 promoter Cre (RIPCre) recombinase or in all neuron using Nestin promoter Cre (NesCre) demonstrated hypothalamic dysfunction [102][103][104].…”
Section: Hypothalamusmentioning
confidence: 99%